IDENTIFIKASI DAN PERAN STAKEHOLDER DALAM PENGEMBANGAN INFRASTRUKTUR KAWASAN WISATA PATUNG CRISTO REI, DILI, TIMOR LESTE - I Nengah Sinarta; Wayan Runa; Ika Wahyuni; Jose Manuel Maniquin (Universitas Warmadewa, 2022)
Timor Leste, which is a new country, is trying to develop tourism as a strategy for community economic development. By developing tourism it is hoped that it will encourage investment in infrastructure, generate income for the country and direct and indirect employment involvement around the region. One of the tourist attractions that want to be developed is the Cristo Rei Statue area which is located on Fatukama hill, Dili City.In 2000 the Government of the Republica Democratica de Timor-Leste had planned to rehabilitate or develop the Cristo Rei Statue as an icon of the City of Dili. Currently, supporting infrastructure for the area has been built, such as parking areas, toilets, trash cans and rest areas. The condition of the infrastructure that is being built is currently damaged and lacks maintenance. Through this PKM, it is hoped that it will be able to identify the condition of the existing infrastructure in the area of ​​the Cristo Rei Statue and be able to increase the role of stakeholders in efforts to maintain and develop infrastructure.